Influence of social networking on Malaysian female secondary students: a qualitative study across three schools - Thang, Siew Ming; Noorizah Mohd Noor; Ng, Lay Shi; Adzuhaidah Md Taha; Noor Baizura Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2017)
Social networking (SN) allows individuals to make connections with each other for both social and business purposes. The purpose of this research study is to find out the influence of SN on students from three Malaysian secondary schools by comparing their attitudes and behaviour towards SN besides finding out whether they are aware of the risks and danger involved, and how they handle them. These schools are all normal day schools and are located in three different types of school environments in Selangor and Kuala Lumpur namely: urban, suburban and rural. Focus groups interviews were conducted on these students who were asked to give their response to seven scenarios depicting negative situations involving SN such as texting, cyberbullying, and hacking and identity theft. The findings revealed that these students were not very different from those in the west in that they are aware of risks involving in SN and will stay clear of risky behaviours. However, students in these three schools handled the problems related to SN in a more direct manner compared to the elite students in Thang et al.’s (2016) study. In particular, students in School C which is a rural school seemed to be less perturbed over the negative consequences of SN compared to students in the other schools.